A internacionalização do Banco do Brasil: produtos e serviços financeiros do Brasil para o mundo - Scaramussa, Giovana Leão Borin (2010)
For the sake of globalization was possible to verify not only the transit of goods but a range of services which can sometimes manage them or can sometimes be offered exclusively. Theories which used to place the product as the center of analysis began also offering valuable insights for the third sector generating new opportunities for review. The focus of this thesis, directed to financial services and represented by the banking market, comes from what is presented as a tendency, not only in academia but also in transactions in the world today. Additionally, the strategic management of bank´s internationalization has not been object of systematic research, especially in Brazil where the sector stands out as what attracts the foreign investors' confidence to the country. The national banking system is solid, competitive, technologically advanced, modern and transparent which becomes a model for the rest of the world. Banco do Brasil was chosen because of its type (mixed-economy), experience, strength, strong brand, as well as his contribution to the history and present of the country. It has achieved the oldest international movement in Brasil which can contribute to a revealing thesis. Considering the aspects mentioned, is appropriated to say this case study aimed to know the history of the Banco do Brasil´s internationalization and also to understand how it, a large store of financial products and services, equalizes it strategies for global standardization and local adaptation in the process of international expansion. In search of answers to these questions were interviewed by telephone people directly involved, and were used semi-structured questionnaires. The development of this study also included a reading of the Day´s (1990) matrix analysis, which highlights some strategic elements that can be assessed at the time a company must decide whether (and how should) compete in global markets: Strategic Orientation, Marketing, Operations and Technology, Human Resources and Sustainability. Based on the results, could be inferred that the analyzed bank's strategy is characterized as transnational, according to the Hill´s (1997) concept. In addition to this data collection and analysis was aimed to experience the perception of the major leaders of the Banco do Brasil about the performance of internationalization by completing a questionnaire, sent it by email. Probably due to the many recent changes arising from the process´ intensification, the aspects evaluated around the Bank´s international performance did not have a consensus by the managers. Data analyzed through documents, content and categories indicated that Banco do Brasil has shown a slow international expansion over the nearly 70 years of his path but today the goals suffered a major boost. The greater consensus, indeed, is in the efforts directed at transforming the institution into a global bank.